Avelumab versus docetaxel in patients with platinum-treated advanced non-small-cell lung cancer (JAVELIN Lung 200): an open-label, randomised, phase 3 study. Issue 11 (November 2018) - Barlesi, Fabrice; Vansteenkiste, Johan; Spigel, David; Ishii, Hidenobu; Garassino, Marina; de Marinis, Filippo; Özgüroğlu, Mustafa; Szczesna, Aleksandra; Polychronis, Andreas; Uslu, Ruchan; Krzakowski, Maciej; Lee, Jong-Seok; et al.
Summary: Background: Antibodies targeting the immune checkpoint molecules PD-1 or PD-L1 have demonstrated clinical efficacy in patients with metastatic non-small-cell lung cancer (NSCLC). In this trial we investigated the efficacy and safety of avelumab, an anti-PD-L1 antibody, in patients with NSCLC who had already received platinum-based therapy. Methods: JAVELIN Lung 200 was a multicentre, open-label, randomised, phase 3 trial at 173 hospitals and cancer treatment centres in 31 countries. Eligible patients were aged 18 years or older and had stage IIIB or IV or recurrent NSCLC and disease progression after treatment with a platinum-containing doublet, an Eastern Cooperative Oncology Group performance status score of 0 or 1, an estimated life expectancy of more than 12 weeks, and adequate haematological, renal, and hepatic function. Participants were randomly assigned (1:1), via an interactive voice-response system with a stratified permuted block method with variable block length, to receive either avelumab 10 mg/kg every 2 weeks or docetaxel 75 mg/m 2 every 3 weeks. Randomisation was stratified by PD-L1 expression (≥1% vs <1% of tumour cells), which was measured with the 73–10 assay, and histology (squamous vs non-squamous). The primary endpoint was overall survival, analysed when roughly 337 events (deaths) had occurred in the PD-L1-positive population. Efficacy was analysed in all PD-L1-positive patients (ie, PD-L1 expression in ≥1% of tumour cells) randomly assigned to study treatment (the primary analysis population) and then in all randomly assigned patients through a hierarchical testing procedure. Safety was analysed in all patients who received at least one dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT02395172 . Enrolment is complete, but the trial is ongoing. Findings: Between March 24, 2015, and Jan 23, 2017, 792 patients were enrolled and randomly assigned to receive avelumab (n=396) or docetaxel (n=396). 264 participants in the avelumab group and 265 in the docetaxel group had PD-L1-positive tumours. In patients with PD-L1-positive tumours, median overall survival did not differ significantly between the avelumab and docetaxel groups (11·4 months [95% CI 9·4–13·9] vs 10·3 months [8·5–13·0]; hazard ratio 0·90 [96% CI 0·72–1·12]; one-sided p=0·16). Treatment-related adverse events occurred in 251 (64%) of 393 avelumab-treated patients and 313 (86%) of 365 docetaxel-treated patients, including grade 3–5 events in 39 (10%) and 180 (49%) patients, respectively. The most common grade 3–5 treatment-related adverse events were infusion-related reaction (six patients [2%]) and increased lipase (four [1%]) in the avelumab group and neutropenia (51 [14%]), febrile neutropenia (37 [10%]), and decreased neutrophil counts (36 [10%]) in the docetaxel group. Serious treatment-related adverse events occurred in 34 (9%) patients in the avelumab group and 75 (21%) in the docetaxel group. Treatment-related deaths occurred in four (1%) participants in the avelumab group, two due to interstitial lung disease, one due to acute kidney injury, and one due to a combination of autoimmune myocarditis, acute cardiac failure, and respiratory failure. Treatment-related deaths occurred in 14 (4%) patients in the docetaxel group, three due to pneumonia, and one each due to febrile neutropenia, septic shock, febrile neutropenia with septic shock, acute respiratory failure, cardiovascular insufficiency, renal impairment, leucopenia with mucosal inflammation and pyrexia, infection, neutropenic infection, dehydration, and unknown causes. Interpretation: Compared with docetaxel, avelumab did not improve overall survival in patients with platinum-treated PD-L1-positive NSCLC, but had a favourable safety profile. Funding: Merck and Pfizer.